TSL031 : Listening and speaking I / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2018)
This course is designed on the assumption that the students already have the basic listening and speaking skills that need to be developed and refined through listening for main ideas and details, note taking, making predictions, guessing meaning from context, and making inferences through various listening materials. The speaking activities, which are in the form of discussions and speeches, will incorporate several verbal communicative strategies and elements of pronunciation.